Cytotoxic effects of oosporein isolated from endophytic fungus Cochliobolus kusanoi - Ramesha, Alurappa; Venkataramana, M.; Nirmaladevi, Dhamodaran; Gupta, Vijai K.; Chandranayaka, S.; Srinivas, Chowdappa (Frontiers in Microbiology, 2015)
In the present study, oosporein, a fungal toxic secondary metabolite known to be a toxic agent causing chronic disorders in animals, was isolated from fungus Cochliobolus kusanoi of Nerium oleander L. Toxic effects of oosporein and the possible mechanisms of cytotoxicity as well as the role of oxidative stress in cytotoxicity to Madin-Darby canine kidney kidney cells and RAW 264.7 splene cells were evaluated in vitro. Also to know the possible in vivo toxic effects of oosporein on kidney and spleen, Balb/C mouse were treated with different concentrations of oosporein ranging from 20 to 200 μM). After 24 h of exposure histopathological observations were made to know the effects of oosporein on target organs. Oosporein induced elevated levels of reactive oxygen species (ROS) generation and high levels of malondialdehyde, loss of mitochondrial membrane potential, induced glutathione hydroxylase (GSH) production was observed in a dose depended manner. Effects oosporein on chromosomal DNA damage was assessed by Comet assay, and increase in DNA damage were observed in both the studied cell lines by increasing the oosporein concentration. Further, oosporein treatment to studied cell lines indicated significant suppression of oxidative stress related gene (Superoxide dismutase1 and Catalase ) expression, and increased levels of mRNA expression in apoptosis or oxidative stress inducing genes HSP70, Caspase3, Caspase6, and Caspase9 as measured by quantitative real time-PCR assay. Histopathological examination of oosporein treated mouse kidney and splenocytes further revealed that, oosporein treated target mouse tissues were significantly damaged with that of untreated sam control mice and these effects were in directly proportional to the the toxin dose. Results of the present study reveals that, ROS is the principle event prompting increased oosporein toxicity in studied in vivio and in vitro animal models. The high previlance of these fungi in temperate climates further warrants the need of safe food grain storage and processing practices to control the toxic effects of oosporein to humans and live stock.